2018
DOI: 10.1007/s11356-018-3345-8
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile fish caging as a tool for assessing microplastics contamination in estuarine fish nursery grounds

Abstract: Estuaries serve as nursery grounds for many marine fish species. However, increasing human activities within estuaries and surrounding areas lead to significant habitat quality degradation for the juveniles. In recent years, plastic pollution has become a global environmental issue as plastic debris are found in all aquatic environments with potential adverse impacts on marine biota. Given the important ecological role of estuaries and implications of microplastics (MP) in ecosystems, here we assess the occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Alternative experimental approaches, such as exposure studies translocating organisms within mesh cages, also provide opportunities to identify how different species respond to different MP levels in the environment, as well as whether previous exposure to MPs may impact susceptibility to future exposure. Similar studies have already been completed in marine systems for blue mussel ( Mytilus edulis , Mytilidae) (Kazour & Amara, 2020) and European flounder ( Platicthys flesus , Pleuronectidae) (Kazour et al, 2018) and are another promising experimental framework for future MP research in freshwater fishes.…”
Section: Future Perspectivesmentioning
confidence: 68%
“…Alternative experimental approaches, such as exposure studies translocating organisms within mesh cages, also provide opportunities to identify how different species respond to different MP levels in the environment, as well as whether previous exposure to MPs may impact susceptibility to future exposure. Similar studies have already been completed in marine systems for blue mussel ( Mytilus edulis , Mytilidae) (Kazour & Amara, 2020) and European flounder ( Platicthys flesus , Pleuronectidae) (Kazour et al, 2018) and are another promising experimental framework for future MP research in freshwater fishes.…”
Section: Future Perspectivesmentioning
confidence: 68%
“…The global scientific community intensified its focus into MP pollution after early reports in 2004 on detecting MP in sea water and sediments. Researchers have since reported evidence of microplastic contamination seemingly everywhere, e.g., lakes and rivers, beverages, and food supplies (Kazour et al 2018). Although the number of publications on microplastics has increased rapidly in recent years, a standardized procedure for identification/quantification of MP is still lacking, and methodologies used by different research groups vary widely, resulting in largely incomparable data between studies (Renner et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In their study of seven different North Sea fish species, Foekema et al (2013) were not able to verify any fundamental effect of MP ingestion on the condition of the MP-feeding fish, originating from five of the seven species under investigation. In an assessment of MP uptake by wild and caged juvenile European flounder Platichthys flesus, Kazour et al (2018) also found no significant correlation between the condition and the number of MP particles taken up at different sampling sites in the eastern English Channel. In an Argentinian estuary, a similar observation was made by Arias et al (2019) who did not detect statistically significant differences in the condition of individuals of the whitemouth croaker Micropogonias furnieri with plastic in their GIT in comparison to individuals without MP particles.…”
Section: Impact Of Ingestionmentioning
confidence: 83%
“…As the focus of this literature review is entirely on in-situ studies, it will report exclusively on the MP-related impacts investigated in those studies under consideration; the analysis of potential effects of MP-ingestion was, however, performed rather infrequently (in 11 of 90 studies). The majority of these studies investigated the impact of MP in the GIT on the condition of the fish based on morphometrics (Supplementary Material): eight studies assessed the condition based on Fulton's condition factor K (Fulton, 1904;Foekema et al, 2013;Rummel et al, 2016;Mizraji et al, 2017;Cardozo et al, 2018;Compa et al, 2018;Kazour et al, 2018;McGoran et al, 2018;Arias et al, 2019), two more studies (Ramos et al, 2012;Dantas et al, 2019) made use of the formula of Richardson's condition factor CF (Richardson et al, 2011). The outcomes of these investigations are equivocal; taking into consideration only the seven reports in which Fulton's K was calculated, one found a statistical significant difference between MP-feeding and non-feeding individuals (Cardozo et al, 2018).…”
Section: Impact Of Ingestionmentioning
confidence: 99%